Creativity in public relations / Andy Green; Chartered Institute of Public Relations. - Green, Andy, 1958-
The subject of creativity in public relations is something of an enigma - while the creative element is considered crucial, it remains an abstract concept where no substantial guidance is provided. Andy Green's book seeks to redress this situation.